Kupffer cell-monocyte communication is essential for initiating murine liver progenitor cell-mediated liver regeneration - Elsegood, Caryn; Chan, C.; Degli-Esposti, M.; Wikstrom, M.; Domenichini, A.; Lazarus, K.; van Rooijen, N.; Ganss, R.; Olynyk, John; Yeoh, G. (John Wiley and Sons Inc., 2015)
Liver progenitor cells (LPCs) are necessary for repair in chronic liver disease because the remaining hepatocytes cannot replicate. However, LPC numbers also correlate with disease severity and hepatocellular carcinoma risk. Thus, the progenitor cell response in diseased liver may be regulated to optimize liver regeneration and minimize the likelihood of tumorigenesis. How this is achieved is currently unknown. Human and mouse diseased liver contain two subpopulations of macrophages with different ontogenetic origins: prenatal yolk sac-derived Kupffer cells and peripheral blood monocyte-derived macrophages. We examined the individual role(s) of Kupffer cells and monocyte-derived macrophages in the induction of LPC proliferation using clodronate liposome deletion of Kupffer cells and adoptive transfer of monocytes, respectively, in the choline-deficient, ethionine-supplemented diet model of liver injury and regeneration. Clodronate liposome treatment reduced initial liver monocyte numbers together with the induction of injury and LPC proliferation. Adoptive transfer of monocytes increased the induction of liver injury, LPC proliferation, and tumor necrosis factor-a production. Conclusion: Kupffer cells control the initial accumulation of monocyte-derived macrophages. These infiltrating monocytes are in turn responsible for the induction of liver injury, the increase in tumor necrosis factor-a, and the subsequent proliferation of LPCs.